Broiler Farmersâ Behavior in Administering Antibiotic and Types of Antibiotic Content in Commercial Feed (A Case Study) - Wasnaeni, Yulia; Iqbal, Achmad; Ismoyowati, Ismoyowati (ANIMAL PRODUCTION, 2015)
Abstract. The objective of this research was to describe broiler farmersâ behavior including knowledge level, attitude, antibiotic practice and analysis of the antibiotic content in broiler chicken commercial feed. Survey method was conducted with purposive and random sampling, applying Nomogram Harry King to determine total sample. Ninety-six farmers met the sampling criteria, comprising 33 respondent farmers along with survey and feed sampling in each farmer. Interview and questioner result on knowledge level and farmersâ attitude and observation on farmers practice in administering antibiotic were subject to description in data tabulation. Laboratory analysis result using Bioassay method on antibiotic content in feed was described in data tabulation. Broiler farmers in Pengadegan municipality, Purbalingga Regency generally showed moderate knowledge level (60% above average, 40% under average). Farmers with supportive attitude on good antibiotic administration was 48.48%, while those less supportive reached 51.52%. Farmersâ level of obedience in proper antibiotic practices was only 21.21%, almost half (45.45%) defiled the proper antibiotic administration. Most farmers (96.97%) used commercial feed containing AGP (Antibiotic Growth Promoter) not recommended by government, namely penicillin, kanamycin, erythromycin andoxytetracycline. Farmer administered overdosed antibiotic as growth booster, anti-stress, disease control and medication. Research concluded that most broiler farmers violated the rules of antibiotic practices, in which overdosed content was administered to stimulate growth, anti-stress, disease control and medication. Antibiotic as growth booster was contained in feed. Commercial broiler feed (complete feed) contained four types of antibiotic, namely penicillin, kanamycin, erythromycin andoxytetracycline.Â Key words:Â  Farmer practice, broiler, Â antibioticsÂ Abstrak. Tujuan penelitian ini adalah menggambarkan perilaku peternak broiler mencakup tingkat pengetahuan, sikap, penggunaan antibiotik, dan analisa kadar antibiotik pada pakan komersial broiler. Metode survey dilakukan dengan sampling acak bertujuan dengan Nomogram Harry King untuk menentukan total sampel. Sembilan puluh enam peternak memenuhi kriteria, mencakup 33 responden peternak dengan survey dan sampel pakan untuk setiap peternak. Hasil interview dan kuesioner tentang tingkat pengetahuan dan perilaku peternak dalam menggunakan antibiotik dideskripsikan dalam tabulasi data. Hasil analisa laboratorium menggunakan metode Bioassay untuk kandungan antibiotik dalam pakan disajikan pada tabulasi data. Peternak broiler di Kecamatan Pengadegan, Kabupaten Purbalingga umumnya memiliki tingkat pengetahuan sedang (60% diatas rata-rata, 40% dibawah rata-rata). Peternak dengan sikap mendukung penggunaan antibiotik sebanyak 48,48%, sedangkan yang kurang mendukung sebanyak 51,52%. Tingkat kepatuhan peternak pada penggunaan antibiotik yang benar hanya 21,21%, hampir separuh (45,45%) tidak mematuhi penggunaan antibiotik yang benar. Sebagian peternak (96,97%) menggunakan pakan komersial yang mengandung AGP (Antibiotic Growth Promotor) yang tidak direkomendasikan oleh pemerintah, yaitu penisilin, kanamisin, eritromisin andoksitetrasiklin. Peternak menggunakan antibiotik melebihi dosis untuk memacu pertumbuhan, sebagai anti stres, mengendalikan penyakit dan pengobatan. Penelitian menyimpulkan bahwa sebagian besar peternak broiler melanggar aturan penggunaan antibiotik, dimana kandungan yang overdosis digunakan untuk memacu pertumbuhan, sebagai anti stres, mengendalikan penyakit, dan pengobatan. Antibiotik sebagai pemacu pertumbuhan terkandung pada pakan. Pakan broiler komersial (complete feed) mengandung empat jenis antibiotik yaitu penisilin, kanamisin, eritromisin andoksitetrasiklin.Â Kata kunci: perilaku peternak, broiler, antibiotik